2022
DOI: 10.1186/s12872-022-02631-8
|View full text |Cite
|
Sign up to set email alerts
|

Short-term/long-term prognosis with or without beta-blockers in patients without heart failure and with preserved ejection fraction after acute myocardial infarction: a multicenter retrospective cohort study

Abstract: Background The role of beta-blockers in acute myocardial infarction patients without heart failure and with preserved left ventricular ejection fraction (LVEF ≥ 50%) is unknown. Our study aimed to retrospectively analyze the associations of beta-blockers on such patients. Methods This is a multicenter, retrospective study. After screening 5,332 acute myocardial infarction patients, a total of 2519 patients without heart failure and with LVEF ≥ 50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Malmberg et al [29] also found the in-hospital mortality to be significantly higher when CABG was performed for patients with AMI, compared with patients with stable coronary artery disease. However, another study indicated that β blockers might not be related to the all-cause mortality in patients with AMI [30]. In our study, it seemed that the assessment of GLR is of more significant concern in patients have not received the…”
Section: Plos Onementioning
confidence: 55%
“…Malmberg et al [29] also found the in-hospital mortality to be significantly higher when CABG was performed for patients with AMI, compared with patients with stable coronary artery disease. However, another study indicated that β blockers might not be related to the all-cause mortality in patients with AMI [30]. In our study, it seemed that the assessment of GLR is of more significant concern in patients have not received the…”
Section: Plos Onementioning
confidence: 55%
“…Three models were constructed: Model 1 was unadjusted, Model 2 was adjusted for age, TDI, sex, smoking, ethnicity, education level, and alcohol use. In addition, the IPTW technique harmonizes the distribution of propensity scores across various cohorts, neutralizing the influences of confounding variables (Neumann and Billionnet, 2016;Wen et al, 2022). To minimize the influence of confounding factors on the outcomes, we employed the COX model after IPTW to verify the association between air pollution and AD.…”
Section: Statistical Analysesmentioning
confidence: 99%